Mohon dibantu kak:)Hari ini dikumpulin
penjelasan:
f(x) = 2x – 1
g(x) = frac{x + 3}{2 – x}
2−x
x+3
(f o g)(x) = f(g(x))
(f o g)(x) = 2 g(x) – 1
(f o g)(x) = 2 left(frac{x + 3}{2 – x}right) – 12(
2−x
x+3
)−1
(f o g)(x) = frac{2x + 6}{2 – x} – frac{2 – x}{2 – x}
2−x
2x+6
−
2−x
2−x
(f o g)(x) = frac{2x + 6 – 2 + x}{2 – x}
2−x
2x+6−2+x
(f o g)(x) = frac{3x + 4}{2 – x}
2−x
3x+4
Misal
(f o g)(x) = y
frac{3x + 4}{2 – x}
2−x
3x+4
= y
3x + 4 = y(2 – x)
3x + 4 = 2y – yx
yx + 3x = 2y – 4
x(y + 3) = 2y – 4
x = frac{2y – 4}{y + 3}
y+3
2y−4
(f o g)⁻¹ (x) = frac{2x – 4}{x + 3}
x+3
2x−4
Cara lain
f(x) = frac{ax + b}{cx + d}
cx+d
ax+b
maka
f⁻¹ (x) = frac{-dx + b}{cx – a}
cx−a
−dx+b
Jadi jika
(f o g)(x) = frac{3x + 4}{2 – x}
2−x
3x+4
(f o g)(x) = frac{3x + 4}{-x + 2}
−x+2
3x+4
maka
(f o g)⁻¹ (x) = frac{-2x + 4}{-x – 3}
−x−3
−2x+4
(f o g)⁻¹ (x) = frac{-(2x – 4)}{-(x + 3)}
−(x+3)
−(2x−4)
(f o g)⁻¹ (x) = frac{2x – 4}{x + 3}
x+3
2x−4